Exploring Teachers’ Enabling and Inhibiting Factors in Using Mobile Teaching Platform with Technology Readiness Index 2.0 - Krismiyati Krismiyati (Teknodika, 2025)
In this digital era, teachers, as the main actors in delivering instruction at the school level, need to keep up with the new technology that could develop their competence. The Indonesian government has launched an application called Platform Merdeka Mengajar as an episode of Merdeka Belajar. Introducing and encouraging the teachers to utilize the application is done through national and regional education authorities. Therefore, it is vital to understand better what influences teachers to use the application. This study aims to examine the factors that motivate and inhibit primary school teachers from using Platform Merdeka Mengajar application investigated through the Technology Readiness Index 2.0 (TRI 2.0) constructs. It is a preliminary study exploring the use of the platform provided by the government to support teachers' professional development. This study uses a quantitative approach with a survey design. The instrument consists of 16 items adapted from TRI 2.0. This study involves 303 primary school teachers in Boyolali. Once the data is collected, the data analysis begins by looking at the teachers' demographic information and the descriptive statistics of each factor being investigated. The result of the study suggests that two constructs in TRI 2.0 indeed motivate the teachers to utilize the government-provided application. Surprisingly, the inhibiting factors do not significantly hinder teachers from using the application. Limitations of the study and suggestions for further research are also described in the conclusion section.